Geochemical characteristics and origins of natural gases in Yinggehai and Qiongdongnan Basins of South China Sea - Huang Qianfeng; Lyu Chengfu; Pang Weixin; Wu Tao; Li Qianzhe; Xiao Yueye (Scientific Reports)
Abstract DF13-2 and YC13-1 are two large gas fields found in Yinggehai and Qiongdongnan Basins, respectively, and the gas-source correlation is a very challenging scientific exercise due to the similarity of their hydrocarbon isotoperatios and gas dryness. In this study, the chemical and isotopic compositions of natural gases (including rare gases and bulk gases) and the biomarkers of condensate were comprehensively integrated to identify their origins. The gases from the two fields are composed primarily of methane (87–91%), and isotope ratios of hydrocarbon compounds exhibit a thermogenic origin, with δ13C1 values ranging from − 40.7 to 35.0‰, and δ13C2 from − 27.0 to − 25.4‰. There are small yet distinct differences in the genetic characteristics of CH4 He, Ar, CO2, N2 and condensate between the samples from two regions. The δ13C1 values of DF13-2 (− 36.8 to − 33.7‰) are slightly larger than those (− 40.7 to − 35.5‰) of YC13-1, suggesting a slightly higher thermal maturity in DF13-2 field. In addition, DF13-2 gases contain lower Ar (0.0096–0.016%) and He (11–15 ppm). The 3He/4He ratios range from 3.31 × 10−8 to 7.72 × 10−8, indicating a typical crustal origin, likely representative of pristine source-rock signatures. The gases have higher N2 (8.4–9.66%) but lower CO2 contents (0.10–0.36%), which are co-generated with the thermogenic hydrocarbon gases. The condensate coexisted with gas contains abundant terrestrial-derived oleanane but a low abundance of bicadinanes. These characteristics correlate well with the Miocene neritic shales in Yinggehai Basin. Fractures associated with the diapiric activity provide key conduits for gas up-migration into the Huangliu Formation reservoir, implying that the flank of a diapiric structure is a favorable site for gas accumulation. In contrast, the gases from YC13-1 field show lower N2 but higher CO2 amounts. He and Ar abundances are both higher with a small amount contribution (2–9%) of mantle-derived He. The elevated amounts of mantle-derived 3He may come from mantle-enriched groundwater circulating in the petroleum system. The coexisted condensate is rich in terrestrial biomarkers such as oleanane and bicadinane, which is significantly different from DF13-2 condensate, and has a close affinity with the coal-bearing source rocks of the Oligocene Yacheng Formation. Unconformities and faults serve as important conduits for lateral and vertical migration from the source rocks to the traps. This suggests that short-distance migration and source facies control the distribution of the natural gases in Qiongdongnan Basin. This study provides novel insights into the origin and accumulation model of natural gases in Yinggehai and Qiongdongnan Basins.